2003
DOI: 10.1081/bio-120023157
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts Cultured from Osteoporotic Bone: A Comparative Investigation on Human and Animal‐Derived Cells

Abstract: In vitro studies on pathophysiology and innovative treatments of many orthopaedic diseases, based on the investigations of cells from pathologic skeletal tissues, greatly improve basic knowledge of osteoporosis. Primary osteoblast (OB) cultures derived from osteopenic bone from different species (human, rat, sheep) were compared to assess the differences that should be taken into account when performing in vitro biocompatibiliy tests or investigating pharmacological and physical treatments. Primary OB were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Moreover, in our study, PGE 2 failed to significantly affect OPG gene expression whereas other studies found an inhibitory effect [Brandstrom et al, 1998;Sakata et al, 2002;Liu et al, 2006]. Different cell sources and/or different cell culture environments might explain these apparently opposite results [Torricelli et al, 2003]. In this regard, Hofbauer et al [1998] have suggested that the osteoblastic cell type seems to determine the response capacity to a hormone or cytokine.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, in our study, PGE 2 failed to significantly affect OPG gene expression whereas other studies found an inhibitory effect [Brandstrom et al, 1998;Sakata et al, 2002;Liu et al, 2006]. Different cell sources and/or different cell culture environments might explain these apparently opposite results [Torricelli et al, 2003]. In this regard, Hofbauer et al [1998] have suggested that the osteoblastic cell type seems to determine the response capacity to a hormone or cytokine.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, species‐specific effects of the immunosuppressants are probable, due to their individual mechanisms of action. Therefore, a transfer of results from animal experiments seems problematic [34,35]. This study analysed the effects of tacrolimus, cyclosporin A and sirolimus for the first time independently of co‐medications and underlying diseases in vitro , using the human osteoblast cell line MG63 [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These differences were most likely related to the cell source and phenotype responding to the given experimental conditions. [17][18][19][20][21] For instance, cell cultures using osteoblasts and mesenchymal stem cells derived from different species on microstructured titanium surfaces showed that cell reactions were influenced by surface chemistry and each cell type displayed different preferences in terms of chemical surface properties for optimal function, 22 while human bone marrow stromal cells derived from iliac crest and alveolar bone were shown to exhibit individual characteristics in terms of differentiation potential depending on their anatomical location. 23 In addition, preliminary experiments conducted by the own group revealed cell source-dependent differences in cell adhesion and morphogenesis between human mesenchymal stem cells and primary human osteoblasts in threedimensional scaffolds.…”
mentioning
confidence: 99%